2021
DOI: 10.1007/s40472-021-00323-4
|View full text |Cite
|
Sign up to set email alerts
|

Lung Transplant from ECMO: Current Results and Predictors of Post-transplant Mortality

Abstract: Purpose of Review We examined data from the last 5 years describing extracorporeal life support (ECLS) as a bridge to lung transplantation. We assessed predictors of survival to transplantation and post-transplant mortality. Recent Findings The number of lung transplants performed worldwide is increasing. This is accompanied by an increase in the type of patients being transplanted, including sicker patients with more advanced disease. Consequently, there is an increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 29 publications
2
23
1
Order By: Relevance
“…Hemodynamic instability caused by anesthesia induction and surgical manipulations can be balanced with ECMO support. Contrary to the literature [14], the indications for transplantation were not associated with the use of ECMO in this study. This may be because the patient population is relatively small.…”
Section: Discussioncontrasting
confidence: 97%
“…Hemodynamic instability caused by anesthesia induction and surgical manipulations can be balanced with ECMO support. Contrary to the literature [14], the indications for transplantation were not associated with the use of ECMO in this study. This may be because the patient population is relatively small.…”
Section: Discussioncontrasting
confidence: 97%
“…Although worsening of illness during long-term BTT may be associated with worse post-transplant outcomes [20], our study found that SAPS II at the time of transplantation were comparable in the groups. Other risk factors such as infection, deconditioning, and ECMO complications also may contribute to the poor prognosis in the long-term BTT group [29]. In this study, interestingly, the requirement for V-A ECMO was more frequent in the LT-BTT group.…”
Section: Plos Onementioning
confidence: 50%
“…4 However, survival in this population is still lower than patients supported as BTT for all-cause lung transplantation. 6 Pulmonary fibrosis was common in our BTT group, indicating these patients may have had end-stage lung disease and were previously listed for transplant before offering ECMO support. In addition, transplanted patients did not receive steroids, had no opportunistic infections, and had decreased ventilatory times.…”
Section: Discussionmentioning
confidence: 86%
“…4 However, survival in this population is still lower than patients supported as BTT for all-cause lung transplantation. 6 Pulmonary fibrosis was common in our BTT Number of patients with data in each category is indicated with (n = x) if there is missing data.…”
Section: Discussionmentioning
confidence: 99%